A study on the impact of polycyclic aromatic hydrocarbons (PAHs) on the risk of liver disease in middle-aged and older adults people based on the CHARLS database - Ying Ni; Wenkai Wang; Yan Xu; Wensheng Zhang (Ecotoxicology and Environmental Safety)
Background: Polycyclic aromatic hydrocarbons (PAHs) are ubiquitous environmental contaminants with potential hepatotoxic effects. However, the relationship between PAHs exposure and liver disease remains incompletely characterized. This study examined PAHs-liver disease associations using China Health and Retirement Longitudinal Study (CHARLS) 2015 data. Methods: We conducted a cross-sectional analysis of 16 types of PAHs across 13 Chinese provinces. Multivariable logistic regression models evaluated associations between individual PAHs and liver disease, adjusting for demographic and health-related covariates. Results: Following comprehensive adjustment, several PAHs (ng/m3) were significantly associated with increased odds of liver disease. Six PAHs showed increased odds: fluorene (OR = 1.13, 95 % CI: 1.01–1.26), anthracene (OR = 1.30, 95 % CI: 1.04–1.62), fluoranthene (OR = 1.04, 95 % CI: 1.00–1.08), benz[a]anthracene (OR = 1.02, 95 % CI: 1.00–1.04), benzo[k]fluoranthene (OR = 1.05, 95 % CI: 1.00–1.11), and benzo[a]pyrene (OR = 1.04, 95 % CI: 1.00–1.08) (all p < 0.05). Conversely, acenaphthylene showed an inverse association (OR = 0.73, 95 % CI: 0.58–0.92). Overall, eight PAH compounds demonstrated statistically significant associations with liver disease. Conclusion: PAHs exposure is significantly associated with liver disease among middle-aged and older Chinese adults. These findings underscore potential hepatotoxic effects of specific PAHs and support environmental policies reducing population exposure. Prospective studies are warranted to establish causality and elucidate underlying mechanisms.